2011
DOI: 10.5539/mas.v5n1p209
|View full text |Cite
|
Sign up to set email alerts
|

Ohmic Processing: Temperature Dependent Electrical Conductivities of Lemon Juice

Abstract: Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 25 publications
3
30
0
Order By: Relevance
“…There are several published patents about the usage of ohmic treatments on several food materials such as; strawberry (Allali et al (2008); Sarang et al (2008); Castro et al (2004)); red apple, golden apple, peach, pear and pineapple ); tomato soup (Jun and Sastry (2005)); apricot and peach purees Icier and Ilicali (2005a)); sour cherry juice (Icier Icier and Ilicali (2004)); tylose (Icier and Ilicali (2005b)); seawater (Assiry et al (2010a); Assiry (2011)); lemon juice (Darvishi et al (2011)); milk (Stancl and Zitny. 2010;Bansal and Chen.…”
Section: Introductionmentioning
confidence: 99%
“…There are several published patents about the usage of ohmic treatments on several food materials such as; strawberry (Allali et al (2008); Sarang et al (2008); Castro et al (2004)); red apple, golden apple, peach, pear and pineapple ); tomato soup (Jun and Sastry (2005)); apricot and peach purees Icier and Ilicali (2005a)); sour cherry juice (Icier Icier and Ilicali (2004)); tylose (Icier and Ilicali (2005b)); seawater (Assiry et al (2010a); Assiry (2011)); lemon juice (Darvishi et al (2011)); milk (Stancl and Zitny. 2010;Bansal and Chen.…”
Section: Introductionmentioning
confidence: 99%
“…At both electric field strengths, the temperature of the medium showed a minor increase throughout the operations (∆T < 2 o C). A minor temperature increase in the medium indicated that distilled water had a lower electrical conductivity compared to brine (Darvishi et al, 2011;Hayashi, 2004). On the other hand, a saline medium caused rapid meat thawing, and the total thawing time decreased to under 1 h (~52 min) for 0.2% NaCl and approached about 30 min for 2% NaCl (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ohmic heating of tomato paste, at 6V/cm, showed that the time taken to reach 96 C was 235s; whereas at 14V/cm the time taken to reach the same temperature was 38s [15] . A bubbling temperature of upto 90 C was reached when grape juice was ohmic heated at 20 to 40 V/cm [17] .…”
Section: Effect Of Temperature and Voltage Gradient On Rate Of Ohmic mentioning
confidence: 99%
“…At 13.33 V/ cm, the time required to heat the pulp without sugar and with 10%, 30% and 50% sugar was observed to be 90s, 120s, 240s and 540s.Similar observation was done at 20 V/cm and 26.66 V/cm. A bubbling temperature of 74 C was reached within 45s when lemon juice was ohmically heated at 30-55V/cm [15] . The ohmic heating of tomato juice at 50-70 V/cm 48s to reach a temperature of 80 C [16] .…”
Section: Effect Of Temperature and Voltage Gradient On Rate Of Ohmic mentioning
confidence: 99%
See 1 more Smart Citation